Ergonomics study on musculoskeletal disorders (MSD) related problems among workers in electronics assembly line - Nik Mohamed, Nik Mohd Zuki; Shalahim, N. S M; Zakri, Ghazali; Ab Rashid, Mohd Fadzil Faisae; Rose, Ahmad Nasser Mohd (2018)
Work-related musculoskeletal disorders (MSDs) are one of the most prevalent occupational health problems, affecting millions of workers every year. Ergonomics is important because our body is stressed by an awkward posture, extreme temperature, or repeated movement which affected the musculoskeletal system. The body may begin to have symptoms such as fatigue, discomfort, and pain, which can be the first signs of a musculoskeletal disorder. Thus, this study aims to analyse the data obtained from electronics company based on workers with manual material handling that involved in the production line. Ergonomics methodology will be used to find out risk and tendency of MSD. This study will suggest improvement in production’s handling by taking care of worker’s safety. The problems related to the assembly and assembly processes were analysed by using WITNESS simulation software, whereas DELMIA simulation software is used to improve human factors working condition. Based from both simulation runs, the assembly line can be further improved in many ways, such as the arrangement of floor layout, workplace condition and machines handling method by the workers. All of these are imperative to improve the working condition which will directly increase the efficiency of the production line. For analysis and implementation stage, the results from the case study experiments will be carried out in the actual manufacturing condition. The main issues that were recorded from the observation and data collection was the delivery always behind the schedule. It was contributed by the human factor which increased the number of rejected parts and slows down the production line. The WITNESS and DELMIA software have successfully improved the overall efficiency of the electronic assembly line. Hence, based on the study, the continuous improvement of the layout design, ergonomic factors and training of operators are possible to be implemented in a larger scale.